Association of pre-pregnancy body mass index with early- and late-onset severe preeclampsia - Dennopporn Sudjai (Elsevier, 2023)
Objective: To determine whether maternal pre-pregnancy body mass index is associated with preeclampsia with severe features, categorized as early- or late-onset. Study design: This retrospective cohort study was conducted at the Department of Obstetrics and Gynecology, Rajavithi Hospital. The inclusion criteria were singleton pregnant women who gave birth at Rajavithi Hospital between January 1, 2015 and October 31, 2019. The study group was pregnant women diagnosed with preeclampsia with severe features while the control group was those without preeclampsia. Body mass index was classified based on The Regional Office for the Western Pacific Region of the World Health Organization criteria. The primary outcome was association of pre-pregnancy body mass index and risk of preeclampsia with severe features, classified by gestational age into early- (< 34 weeks) and late- (≥ 34 weeks) onset preeclampsia. Comparisons were made using the Student's t-test, Chi-square, or Fisher's exact tests, as appropriate. Logistic regression was used to assess associations. Results: There were 589 pregnant women in the control group and 519 women with preeclampsia in the study group. The study group was subdivided into early-onset (32.4 %, 168/519) and late-onset (67.6 %, 351/519) preeclampsia. Women who had preeclampsia with severe features had higher mean pre-pregnancy BMI than those without preeclampsia. Women with class I (63.6 %, 136/214) and II (81.0 %, 111/137) obesity (body mass index, 25.0-29.9 and ≥ 30.0 kg/m2, respectively) had significantly increased risk of preeclampsia with severe features (adjusted odds ratio 2.71, 95 % confidence interval 1.85-4.00 and adjusted odds ratio 3.84, 95 % confidence interval 2.22-6.64, respectively). In preeclampsia subgroup analysis, class I obesity was significantly associated with late-onset severe preeclampsia (adjusted odds ratio 2.02, 95 % confidence interval 1.40-2.93), while class II obesity was significantly associated with both early- and late-onset severe preeclampsia (adjusted odds ratio 1.69, 95 % confidence interval 1.01-2.84 and adjusted odds ratio 2.13, 95 % confidence interval 1.36-3.33, respectively). Conclusions: Class I and II obesity are significantly associated with preeclampsia with severe features. Class I obesity is significantly related to late-onset severe preeclampsia with, whereas class II obesity is associated with both early- and late-onset severe preeclampsia.